SHIFTING POWER: The Impact of Incarceration on Political Representation. (2018) - Remster, Brianna; Kramer, Rory
Abstract: While prisoners cannot vote, they are counted as residents of the often rural legislative districts where they are incarcerated rather than their home districts. We examine the extent to which incarceration shifts the balance of a representative democracy by considering its impact on legislative apportionment. Drawing on data from the Census, Pennsylvania Department of Corrections, and Pennsylvania Redistricting Commission, we develop a counterfactual framework to examine whether removing and returning prisoners to their home districts affects equal representation. Because prisoners are disproportionately African American, we also employ this counterfactual to assess racial differences in the impact of prison gerrymandering. Findings indicate that incarceration shifts political power from urban districts to suburban and rural districts through legislative apportionment. Moreover, non-White communities suffer the most. We conclude by considering how our findings fit a growing literature on the role of mass incarceration in [re]producing racial inequalities in the contemporary United States.